Motivation to Quit Smoking after Acute Coronary Syndrome - Vânia Rocha; Marina Guerra; Marina Lemos; Júlia Maciel; Geoffrey Williams (Acta Médica Portuguesa, 2017)
Introduction: Self-Determination Theory explores the process through which a person acquires motivation to initiate new behaviours related to health and to maintain them over time. This study aimed to determine the overall fit of Self-Determination Theory Model for Health Behavior to the data obtained from a sample of smokers hospitalized with acute coronary syndrome, and to identify the predictors of smoking status six months after clinical discharge. Material and Methods: The sample included 110 participants, regular smokers, hospitalized due to acute coronary syndrome. Questionnaires were administered to assess autonomous self-regulation, perceived competence, family support, depressive symptoms and meaning in life. Participants were asked if they were currently smokers six months after clinical discharge. Results: The results showed that the process variables specified by Self-Determination Theory fit the data well. Perceived competence predicted abstinence from smoking six months after clinical discharge. Discussion: Our findings have similar characteristics to other international samples in which Self-Determination Theory models have been tested. It is important to facilitate perceived competence, as the patients who continue to smoke have shorter length of life. Conclusion: This study highlights the importance of considering clinical interventions based on Self-Determination Theory to facilitate smoking cessation.